2018
DOI: 10.1186/s42408-018-0003-y
|View full text |Cite
|
Sign up to set email alerts
|

Fire effects on a fire-adapted species: response of grass stage longleaf pine seedlings to experimental burning

Abstract: Background: Longleaf pine (Pinus palustris Mill.) seedlings have a morphological "grass stage" that is considered to be an adaptation to frequent surface fire regimes. However, fire can kill longleaf pine seedlings and thus may play an important role in longleaf pine regeneration dynamics. We used a prescribed burn simulation tool designed to treat individual grass stage longleaf pine seedlings with controlled delivery of fire treatments and then measured survival and growth responses through two growing seaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 66 publications
(84 reference statements)
3
20
0
Order By: Relevance
“…For this reason, prescribed fire is an important tool in ongoing longleaf pine restoration efforts. The survival of prescribed burned longleaf pine seedlings is correlated with their size [39], and application of fire is not advocated until after the first growing season following planting [40]. Beyond this developmental stage, survival and vigorous growth among longleaf pine seedlings and saplings that experience severe crown scorch demonstrates the fire-tolerance of this species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, prescribed fire is an important tool in ongoing longleaf pine restoration efforts. The survival of prescribed burned longleaf pine seedlings is correlated with their size [39], and application of fire is not advocated until after the first growing season following planting [40]. Beyond this developmental stage, survival and vigorous growth among longleaf pine seedlings and saplings that experience severe crown scorch demonstrates the fire-tolerance of this species.…”
Section: Discussionmentioning
confidence: 99%
“…Application of prescribed fire among vigorously growing longleaf pine seedlings and saplings may be necessary to insure high light availability and reduce establishment of woody competitors [39][40][41]. The stature of longleaf pine seedlings and saplings predisposes them to complete or nearly complete crown scorch.…”
Section: Introductionmentioning
confidence: 99%
“…For seedlings >7.6 mm in root collar diameter, fire-induced mortality was reported at less than 25% (e.g., [14,17,27]). In a recent experimental study, however, Knapp et al [16] reported that mortality could approach 50% for seedlings with root collar diameters >15 mm under high-intensity burns. Seedling size is an important factor affecting the fire survival of grass stage seedlings, but it remains uncertain if fire survival changes continuously with the size or abruptly with size thresholds.…”
Section: Introductionmentioning
confidence: 97%
“…Despite their well-known fire tolerance, longleaf pine seedlings in the grass stage are far from invulnerable, and high fire-induced mortality has been reported in many studies (e.g., [14][15][16]). During the grass stage, burning often scorches and even consumes the needles around the apical bud.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation